Synthesis, luminescent properties and theoretical calculations of novel orange-red-emitting Ca2Y8(SiO4)6O2:Sm3+ phosphors for white light-emitting diodes. (March 2018) - Chen, Chun-Ting; Lin, Tzu-Jen; Molokeev, Maxim S.; Liu, Wei-Ren
Abstract: The novel orange-red-emitting Ca2 Y8 (SiO4 )6 O2 :Sm 3+ phosphors (CYSO:Sm 3+ ) were synthesized via conventional a solid state reaction. The crystal structure and atomic coordinates of CYSO:Sm 3+ was characterized by Rietveld refinement. Luminesce properties of as-synthesized CYSO:Sm 3+ phosphors are carried out by PL/PLE, decay life time, thermal quenching as well as reflectance spectrometer and LED fabrications. The results indicates that composition-optimized CYSO:1%Sm 3+ exhibits orange-red emission peaks located on 564, 601, 608 and 648 nm attributed to the transitions of 4 G5/2 → 6 H5/2, 4 G5/2 → 6 H7/2, 4 G5/2 → 6 H7/2 and 4 G 5/2 → 6 H9/2, respectively. The decay lifetime of CYSO:Sm 3+ phosphors was in the range of 0.37–1.10 ms. The temperature-dependent photoluminescence is decreased to 80% from room temperature to 150 °C, which is superior to that of commercial red phsophpr-Y2 O3 :Eu 3+ . The results of LED fabrication by combing 405 chips and blue/green phosphors are demonstrated in this study. Finally, from viewpoint of theoretical calculations, band structure and density of state for CYSO and CYSO:Sm 3+ are studied by first principles calculations. All the results indicate that CYSO:Sm 3+ phosphors could be a potential material for white light-emitting diodes. Graphical abstract: Highlights: New Sm 3+ -doped red-emitting phosphor synthesized by a solid-state reaction. Fabrication of UV-LED and phosphors. Luminescence characterizations between experimental and theoretical calculations. Their crystal structure, thermal and luminescent properties are researched.